Polypropylene fiber concrete and preparation method thereof

By adding nano silica and glass powder to the regenerated aggregate and using polypropylene fiber, the problem of deterioration of the mechanical properties and freeze-thaw resistance of concrete for the regenerated aggregate preparation is solved, and higher strength and freeze-resistant properties are achieved , promotes early condensation and durability of concrete.

CN119241140APending Publication Date: 2025-01-03HAINAN SHENGDAO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411135397.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

When preparing concrete, regenerated aggregates produce transverse microcracks and pores during the crushing process, resulting in poor mechanical properties and freeze-thaw resistance of the concrete. The existing technology is difficult to effectively solve this problem.

Method used

Polypropylene fiber concrete formula, including regenerated aggregate, fine aggregate, cement, nano silica and glass powder, is used to prepare concrete with improved microstructure by mixing evenly and adding polypropylene fibers and water reducing agent, and use nanometers Silica and glass powder accelerate hydration rates, fill pores, improve strength and frost resistance.

Benefits of technology

It significantly improves the early strength and freezing resistance of polypropylene fiber concrete, improves the microstructure of concrete, reduces porosity, enhances mechanical properties and freezing and thawing resistance, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241140A_ABST
    Figure CN119241140A_ABST
Patent Text Reader

Abstract

The invention provides polypropylene fiber concrete and a preparation method thereof, and belongs to the technical field of concrete, the polypropylene fiber concrete is prepared by uniformly mixing 320-330 parts by weight of recycled aggregate, 610-620 parts by weight of fine aggregate, 380-390 parts by weight of cement, 1.2-1.5 parts by weight of polypropylene fiber, 1.5-2.0 parts by weight of glass powder, 0.8-1.0 part by weight of nano silicon dioxide, 5-7 parts by weight of a water reducing agent and 170-180 parts by weight of water. Through the synergistic effect of the nano silicon dioxide, the glass powder and the polypropylene fiber, the problems that the mechanical property and the freeze-thaw resistance become poor due to the fact that the recycled aggregate is used for preparing the concrete are effectively solved, recycling of the recycled aggregate is well achieved, and the compression resistance and the freeze-thaw resistance of the prepared polypropylene fiber concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of concrete, and in particular relates to polypropylene fiber concrete and a preparation method thereof. Background Art

[0002] With the continuous acceleration of urban development, the urbanization process is getting faster and faster. At the same time, there are more and more old city renovation projects, which have generated a large amount of abandoned construction waste. In my country, most of the construction waste has not been recycled in a scientific way. Most of the construction waste is treated as garbage, randomly dumped in the open suburbs, or simply landfilled, which has a huge burden on the environment. Therefore, it is necessary to develop how to comprehensively utilize the recycled aggregate made from construction waste. However, since the recycled aggregate is made by crushing the construction waste several times by a crusher. In this process, under the condition of mechanical work, a large number of transverse microcracks and pores will be generated inside the recycled aggregate. The surface has many edges and corners, and the old cement mortar attached to the surface cannot be removed, which will make the microstructure of the recycled aggregate itself worse, so that the recycled aggregate has a large water absorption rate, a large strength discreteness, and a weak bonding surface with the new cement mortar, which seriously affects the physical and mechanical properties and freeze-thaw resistance of the concrete made from it. Therefore, how to solve the problems of poor mechanical properties and freeze-thaw resistance caused by the use of recycled aggregates to prepare concrete has become one of the research hotspots. Summary of the invention

[0003] In view of the above problems, the present invention provides a polypropylene fiber concrete and a preparation method thereof.

[0004] To achieve the above purpose, the technical solution adopted by the present invention is:

[0005] A polypropylene fiber concrete, wherein the raw materials for making the polypropylene fiber concrete include, by weight:

[0006] 320-330 parts of recycled aggregate, 610-620 parts of fine aggregate, 380-390 parts of cement, 1.2-1.5 parts of polypropylene fiber, 1.5-2.0 parts of glass powder and 0.8-1.0 parts of nano silicon dioxide.

[0007] Furthermore, the raw materials for making the polypropylene fiber concrete also include: 5 to 7 parts by weight of a water reducing agent and 170 to 180 parts by weight of water.

[0008] Furthermore, the water reducing agent is a naphthalene-based water reducing agent.

[0009] Furthermore, the recycled aggregate is obtained by crushing, washing and drying construction waste.

[0010] Furthermore, the particle size of the recycled aggregate is 15 to 25 mm.

[0011] A method for preparing the above-mentioned polypropylene fiber concrete, the preparation method is to take all raw materials and mix them evenly to prepare the polypropylene fiber concrete.

[0012] Furthermore, the preparation method comprises the following specific steps:

[0013] Take nano-silicon dioxide and glass powder, add them to part of the water, stir and disperse them to obtain a suspension;

[0014] Take fine aggregate and recycled aggregate in a mixer and stir and mix them evenly, then add cement and stir, then add suspension and stir, then add polypropylene fiber and stir, then add water reducer and remaining water and stir evenly to obtain the polypropylene fiber concrete.

[0015] Furthermore, the stirring time is 30 to 40 seconds after adding the suspension and before adding the polypropylene fiber;

[0016] After adding the polypropylene fiber and before adding the water reducer and the remaining water, the stirring time is 50 to 70 seconds.

[0017] Furthermore, the time for mixing the fine aggregate and the recycled aggregate is 60 to 80 seconds;

[0018] After adding cement and before adding suspension, the stirring time is 60 to 80 seconds.

[0019] Furthermore, the polypropylene fiber concrete is cured for more than 28 days to obtain a concrete specimen.

[0020] The beneficial effects of the polypropylene fiber concrete and the preparation method thereof of the present invention are:

[0021] The present invention simultaneously adds glass powder and nano silicon dioxide into the cement system, thereby improving the microstructure of polypropylene fiber concrete, promoting early dissolution of cement, increasing the alkalinity of the composite system, and facilitating the breaking of high-energy bonds inside the glass powder, thereby increasing the early hydration degree of the glass powder in the composite system; and utilizing the micro-aggregate effect to improve the microstructure of the polypropylene fiber concrete slurry, making the finally prepared polypropylene fiber concrete more compact, and significantly shortening the coagulation time of the composite system through the accelerating coagulation effect, thereby greatly increasing its early strength;

[0022] The present invention can cooperate with each other to accelerate the hydration rate of the bonding material by adding nano-silicon dioxide and glass powder; and utilize the volcanic ash effect of nano-silicon dioxide and glass powder to consume calcium hydroxide crystals, promote cement hydration, and generate CSH gel to fill the pores of cement paste, improve the microstructure of concrete, and reduce porosity; at the same time, the volcanic ash reaction of nano-silicon dioxide and glass powder with broken high-energy bonds and calcium hydroxide increases the content of CSH, thereby improving the strength and frost resistance of the material;

[0023] Nano-silica particles and glass powder particles are small, which can improve particle packing and refine the pore structure, thereby shortening the setting time of concrete, reducing water seepage and segregation of concrete, and improving the cohesion of the mixture in the early state;

[0024] Since nano-silicon dioxide and glass powder can be filled into the internal pores of concrete, the density of the concrete matrix can be improved, which is beneficial to the improvement of the mechanical properties and frost resistance of concrete;

[0025] At the same time, the present invention can reduce the amount of nano silicon dioxide by adding glass powder, which is beneficial to reducing the production cost of polypropylene fiber concrete;

[0026] Although the recycled aggregate needs to be crushed several times when used, which will cause a large number of transverse microcracks and pores inside, and the many edges and corners on the surface, and the old cement mortar attached to the surface that cannot be removed, etc., will deteriorate the microstructure of the recycled aggregate itself, resulting in the deterioration of the mechanical properties and freeze-thaw resistance of the prepared concrete, the present invention can fully fill and improve the microstructure of the recycled aggregate itself by adding a specific amount of nano-silicon dioxide and glass powder, thereby improving the physical and mechanical properties and freeze-thaw resistance of the prepared concrete;

[0027] At the same time, the present invention can greatly reduce the drying shrinkage of concrete and improve durability by adding polypropylene fibers; at the same time, by adding polypropylene fibers, nano-silicon dioxide and glass powder, the tensile and bending resistance of concrete can be improved, and the impermeability and freeze-thaw resistance can be improved;

[0028] The present invention effectively solves the problems of poor mechanical properties and freeze-thaw resistance caused by using recycled aggregate to prepare concrete through the synergistic effect of nano-silicon dioxide, glass powder and polypropylene fiber, realizes the recycling of recycled aggregate well, and improves the compressive strength and freeze-thaw resistance of the prepared polypropylene fiber concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a graph showing the 28-day antioxidant strength of nano-silicon dioxide in Example 6 of the present invention;

[0030] Figure 2 This is a graph showing the mass loss rate of nano-silicon dioxide after 100 freeze-thaw cycles in Example 6 of the present invention;

[0031] Figure 3 This is a graph showing the 28d anti-oxidation strength results of the glass powder in Example 6 of the present invention;

[0032] Figure 4 is a graph showing the mass loss rate of the glass powder in Example 6 of the present invention after 100 freeze-thaw cycles;

[0033] Figure 5 This is a graph showing the 28d anti-oxidation strength results of the polypropylene fiber in Example 6 of the present invention;

[0034] Figure 6 This is a graph showing the mass loss rate of the polypropylene fiber in Example 6 of the present invention after 100 freeze-thaw cycles. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0036] Example 1 A polypropylene fiber concrete and a preparation method thereof

[0037] 1. Formula

[0038] This embodiment is a polypropylene fiber concrete, and its formula is:

[0039] 325kg recycled aggregate with a particle size of 15-25mm, 625kg fine aggregate, 386kg cement, 1.3kg polypropylene fiber, 1.8kg glass powder, 0.9kg nano silicon dioxide, 6kg water reducer (naphthalene water reducer is used in this embodiment) and 176kg water.

[0040] 2. Preparation method

[0041] A method for preparing polypropylene fiber concrete in this embodiment adopts the above formula and includes the following specific steps:

[0042] Take the construction waste and crush it three times with a crusher to a particle size of 15-25 mm, wash and dry it to obtain recycled aggregate for later use;

[0043] Take the fine aggregate and sieve it for later use;

[0044] Take 0.9 kg of nano-silicon dioxide and 1.8 kg of glass powder, add them to 50 kg of water, stir and disperse to obtain a suspension.

[0045] Take 625kg of fine aggregate and 325kg of recycled aggregate and stir them in a mixer for 60s, then add 386kg of cement and stir for 60s, then add the suspension and stir for 40s, then add 1.3kg of polypropylene fiber and stir for 60s, then add 6kg of water reducer and the remaining water, stir evenly, finally pour the evenly stirred concrete mixture into a mold, place it on a vibration table and vibrate it evenly, after vibrating evenly, put it in a standard curing room and cure it for 28d to obtain a concrete specimen, marked as H1.

[0046] The 28d compressive strength of the obtained concrete specimen H1 is 43.5MPa, and the mass loss rate after 100 freeze-thaw cycles is 0.07%.

[0047] Among them, the 28d compressive strength is tested according to the Standard for Test Methods of Mechanical Properties of Ordinary Concrete (GB / T50081-2002);

[0048] The freeze-thaw cycle test is carried out in accordance with the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2009).

[0049] Examples 2 to 5 Polypropylene fiber concrete and preparation method thereof

[0050] Examples 2 to 5 are respectively a polypropylene fiber concrete and a preparation method thereof, which are basically the same as Example 1, except that some process parameters are different, as shown in Table 1:

[0051] Table 1 List of process parameters in Examples 2 to 5

[0052]

[0053] The contents and results of other parts of Examples 2 to 5 are the same as those of Example 1 and will not be repeated here.

[0054] Example 6: Investigation of the formulation of polypropylene fiber concrete

[0055] This example investigates the formulation in the preparation process of the polypropylene fiber concrete in Example 1. During the investigation, the preparation method of the polypropylene fiber concrete is basically the same as the preparation method in Example 1.

[0056] 1. Investigation on the amount of nano-silicon dioxide added

[0057] The same batch of raw materials in Example 1 were used to examine the addition amount of nano-silicon dioxide when it was 0, 0.3, 0.6, 0.9, 1.2, and 1.5 kg (that is, only the addition amount of nano-silicon dioxide in Example 1 was changed, and the amounts of other raw materials and process conditions remained unchanged), and concrete specimens with different nano-silicon dioxide additions were prepared. The 28d compressive strength of the concrete specimens with different nano-silicon dioxide additions and the mass loss rate of 100 freeze-thaw cycles are shown in Tables 2 and Figure 1 to Figure 2 .

[0058] Table 2 Summary of the results of the investigation on the amount of nano-silicon dioxide added

[0059] Nano-silicon dioxide addition amount (kg) 28d compressive strength (MPa) Mass loss rate after 100 freeze-thaw cycles (%) 0 33.6 1.84 0.3 36.9 1.07 0.6 39.7 0.51 0.9 43.5 0.07 1.2 41.6 0.14 1.5 38.5 0.47

[0060] From Table 2 and Figure 1 to Figure 2 It can be seen that the present invention prepares polypropylene fiber concrete with better compressive strength and antifreeze performance by selecting a suitable amount of nano-silicon dioxide addition.

[0061] 2. Investigation of glass powder addition

[0062] The same batch of raw materials in Example 1 were used to examine the addition amount of glass powder of 0, 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0 kg (that is, only the addition amount of glass powder in Example 1 was changed, and the amounts of other raw materials and process conditions remained unchanged), and concrete specimens with different glass powder addition amounts were prepared. The 28d compressive strength and mass loss rate of 100 freeze-thaw cycles of the concrete specimens with different glass powder addition amounts are shown in Tables 3 and Figure 3 to Figure 4 .

[0063] Table 3 Summary of the results of glass powder addition

[0064]

[0065]

[0066] From Table 3 and Figure 3 to Figure 4 It can be seen that the present invention prepares polypropylene fiber concrete with better compressive strength and antifreeze performance by selecting a suitable amount of glass powder added.

[0067] 3. Investigation on the amount of polypropylene fiber added

[0068] The same batch of raw materials in Example 1 were used to examine the addition amount of polypropylene fiber of 0, 0.3, 0.6, 0.9, 1.2, 1.5, 1.8, and 2.1 kg (that is, only the addition amount of polyester fiber in Example 1 was changed, and the amounts of other raw materials and process conditions remained unchanged), and concrete specimens with different addition amounts of polypropylene fiber were prepared. The 28d compressive strength and mass loss rate of 100 freeze-thaw cycles of the concrete specimens with different addition amounts of polypropylene fiber are shown in Tables 4 and Figures 5 and 6 .

[0069] Table 4 Summary of the results of investigation on the amount of polypropylene fiber added

[0070] Polypropylene fiber addition amount (kg) 28d compressive strength (MPa) Mass loss rate after 100 freeze-thaw cycles (%) 0 43.7 1.66 0.3 43.6 1.23 0.6 43.5 0.78 0.9 43.5 0.43 1.2 43.4 0.08 1.5 42.9 0.09 1.8 39.3 0.39 2.1 33.2 0.98

[0071] From Table 4 and Figures 5 and 6 It can be seen that the present invention prepares polypropylene fiber concrete with better compressive strength and antifreeze performance by selecting a suitable amount of polypropylene fiber addition.

[0072] Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A polypropylene fiber concrete, characterized in that: The raw materials for making the polypropylene fiber concrete include, by weight: 320-330 parts of recycled aggregate, 610-620 parts of fine aggregate, 380-390 parts of cement, 1.2-1.5 parts of polypropylene fiber, 1.5-2.0 parts of glass powder and 0.8-1.0 parts of nano silicon dioxide.

2. The polypropylene fiber concrete according to claim 1, characterized in that: The raw materials for making the polypropylene fiber concrete also include: 5 to 7 parts by weight of a water reducing agent and 170 to 180 parts by weight of water.

3. The polypropylene fiber concrete according to claim 2, characterized in that: The water reducing agent is a naphthalene-based water reducing agent.

4. The polypropylene fiber concrete according to any one of claims 1 to 3, characterized in that: The recycled aggregate is obtained by crushing construction waste, washing it and drying it.

5. The polypropylene fiber concrete according to claim 4, characterized in that: The particle size of the recycled aggregate is 15 to 25 mm.

6. A method for preparing polypropylene fiber concrete according to any one of claims 1 to 5, characterized in that: The preparation method comprises mixing all raw materials to obtain the polypropylene fiber concrete.

7. The method for preparing polypropylene fiber concrete according to claim 6, characterized in that: The preparation method comprises the following specific steps: Take nano-silicon dioxide and glass powder, add them to part of the water, stir and disperse them to obtain a suspension; Take fine aggregate and recycled aggregate and stir and mix them evenly, then add cement and stir, then add suspension and stir, then add polypropylene fiber and stir, then add water reducer and remaining water and stir evenly to obtain the polypropylene fiber concrete.

8. The method for preparing polypropylene fiber concrete according to claim 7, characterized in that: After adding the suspension and before adding the polypropylene fiber, the stirring time is 30 to 40 seconds; After adding the polypropylene fiber and before adding the water reducer and the remaining water, the stirring time is 50 to 70 seconds.

9. The method for preparing polypropylene fiber concrete according to claim 7 or 8, characterized in that: The time for mixing fine aggregate and recycled aggregate is 60 to 80 seconds; After adding cement and before adding suspension, the stirring time is 60 to 80 seconds.

10. The method for preparing polypropylene fiber concrete according to claim 7 or 8, characterized in that: The polypropylene fiber concrete is cured for more than 28 days to obtain a concrete specimen.